Analisis Faktor-Faktor yang Mempengaruhi Audit Delay dengan Audit Tenure Sebagai Variabel Moderasi - Qodar Ranggala; Ihrom Ihrom (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2020)
The purpose of this research is to determine the factors that influence audit delay with audit tenure as a moderating variable. The research data is derived from the annual audited financial statements of manufacturing companies from 2015-2017. The data analysis technique used in this study is the technique of multiple regression analysis with SPSS 20. The results of this research showed that profitability and firm size have a negative effect on audit delay, while solvency has no effect on audit delay, audit tenure does not strengthen the relationship between profitability and audit delay, audit tenure does not strenghten the relationship between solvency and audit delay, and audit tenure strengthens the influence between company size and audit delay.